The Effects of Covid-19 on Food Waste Management: A Qualitative Case Study on Food Lover’s Market - Ncube, Minenhle (The IIE, 2020)
Food waste has been affecting the globe for many years and has been further challenged by the Covid-19 outbreak. A restructuring of the production and consumption of food will have to happen in order to adjust to the new way of life. The aim of this study is to assess the impact that Covid-19 has had on the food waste management behaviours of Food Lover’s Market as well as the South African consumer and explore opportunities that may arise from this pandemic for meaningful and sustainable food waste management. To evaluate Food Lover’s current processes but also explore the changes and adjustments that Food Lover’s has had to make or may be considering due to the pandemic an interview was conducted with a Food Lover’s Market employee and the interview was then analysed and themes and patterns were developed. The results showed that not much has been changed in relation to food waste management due to Covid-19 and revealed that there is opportunity for improvement of systems in the supply chain. To understand and gauge consumer knowledge and behaviour towards the issue, a questionnaire was distributed, and the results revealed that, consumers are not fully aware of the national food waste crisis and may not how to properly manage their waste. This means that there is a gap and opportunity to educate and create awareness on the issue.
Keywords: Retail industry; Sustainable food waste management; Consumer behaviour; Consumer education; Consumer knowledge; Food waste crisis; Meaningful brands; Sustainable brand